Pengaruh Permainan Angka terhadap Kemampuan Berhitung Permulaan Kelompok B - Iin Khoirotul Masruroh; Dwi Nurhayati Adhani; Dewi Mayangsari (PG-PAUD Trunojoyo, 2019)
This study aims to find out how the influence of the numbers play on the initial numeracy ability of group B in Muslimat 03 Roudlotut Tholibin Kindergarten Warukulon. The subjects of this study were 14 children. This study uses a quantitative approach using an experimental method with a pre-experimental design of the Pretest-posttest-Design One-Group design. Data collection techniques used are observation and documentation. The data analysis technique is in the form of non-parametric statistics in the form of a Wilcoxon level test with data from the pretest and posttest assessment results. The results of this study were obtained at the pretest that there were 5 children with undeveloped criteria (BB), and 8 children with criteria still developing (MB), and 1children the criteria developed according to expectations (BSH). Whereas in the posttest study 3 children with criteria for excellent development (BSB), and 8 children with criteria developed according to expectations (BSH), and there were 3 children with criteria still developing (MB). The calculation result using the Wilcoxon level test obtained a value of Tcount Ttable (021) that is T more than T table. So that the decision making is HO (Zero Hypotesis) is rejected and HA (Alternative Hypotesis) is accepted because Thitung Ttable (021). So that there is an influence on the numbers game on the initial numeracy skills at the Muslimat 03 kindergarten Roudlotut Tholibin Warukulon.